2017
DOI: 10.5020/23180714.2017.32.2.180-192
|View full text |Cite
|
Sign up to set email alerts
|

Transexualidade na formação do professor da educação básica: desvelando a realidade brasileira

Abstract: Esse trabalho de pesquisa resulta de uma investigação cuja questão norteadora foi: os professores são preparados, em sua formação acadêmica, para lidar com alunos transexuais? Assim, o objetivo do estudo foi verificar se os cursos de Pedagogia e os Programas Especiais de Formação Pedagógica de Docentes no Brasil têm incorporado em suas propostas curriculares questões relacionadas à transexualidade, bem como identificar as publicações acadêmicas sobre o tema pesquisado. A metodologia empregada foi a análise de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Thus, it is clear that, despite the recognition of transphobia experienced at school, most teachers still have some resistance in addressing the topic of homosexuality and discussing gender issues, which can contribute to prejudice in their classrooms (32)(33)(34)(35)(36) . On this issue, this study showed that some teachers recognize that this must be modified; however, in view of the routine imposed by the institution, they end up reproducing attitudes considered exclusive and prejudiced (31,(37)(38) . On the other hand, there are teachers who only reproduce their role as execution agents through the reproduction of content.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Thus, it is clear that, despite the recognition of transphobia experienced at school, most teachers still have some resistance in addressing the topic of homosexuality and discussing gender issues, which can contribute to prejudice in their classrooms (32)(33)(34)(35)(36) . On this issue, this study showed that some teachers recognize that this must be modified; however, in view of the routine imposed by the institution, they end up reproducing attitudes considered exclusive and prejudiced (31,(37)(38) . On the other hand, there are teachers who only reproduce their role as execution agents through the reproduction of content.…”
Section: Discussionmentioning
confidence: 83%
“…In this perspective, several countries have recognized gender diversity in childhood and youth and making it increasingly visible, recognized and under-serviced by the public policies, including the educational ones. Until recently, the existing national legislation, namely the so-called "gender identity laws", assumed that gender identification was a characteristic only of adults, creating an environment of ignorance and risk for children and their families (31) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations